Anti-windup design for stochastic Markovian switching systems with mode-dependent time-varying delays and saturation nonlinearity. (November 2017) - Qi, Wenhai; Park, Ju H.; Cheng, Jun; Kao, Yonggui; Gao, Xianwen
Abstract: This paper treats the problem of anti-windup design for stochastic Markovian switching systems with mode-dependent time-varying delays and saturation nonlinearity. The anti-windup compensator is designed such that the resulting system with mode-dependent time-varying delays and saturating actuator is stochastically stable and the domain of attraction is maximized. Sufficient conditions for the corresponding problem are proposed in terms of linear matrix inequalities. Finally, an example about R L C serial circuit demonstrates the validity of the proposed results.